The Influence of Green Product, Green Advertising, and Green Brand Awareness on Purchase Intention among Generation Z in Jambi City - Rindiani Rindiani (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of green products, green advertising, and green brand awareness on Purchase Intention among Generation Z in Jambi City. Using a quantitative approach through a survey method, data were collected from 100 Generation Z respondents using a Likert-scale questionnaire. Analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that green products and green brand awareness have a positive and significant effect on Purchase Intention, while green advertising has a positive but insignificant effect. The R² value of 0.661 indicates that the three independent variables can explain 66.1% of the variation in Purchase Intention. This study provides an empirical contribution to the green marketing literature within the local context of Jambi and emphasizes the importance of product quality and brand awareness in driving purchase intention for green products.